Experimental and Numerical Study of Shear Fracture in Brittle Materials with Interference of Initial Double Cracks - Haeri, Hadi; Sarfarazi, Vahab; Marji, Mohammad Fatehi; Hedayat, Ahmadreza; Zhu, Zheming (Acta mechanica solida Sinica, 2016)
A simultaneous experimental and numerical study of shear fracture of concrete-like materials is carried out using Brazilian disc specimens with initial double edge cracks and fourpoint bending beam specimens with double edge-notches. The interference effects of two cracks/notches are investigated through varied ligament angles and crack lengths. It is shown that shear fracturing paths change remarkably with the initial ligament angles and crack lengths. The cracked specimens are numerically simulated by an indirect boundary element method. A comparison between the numerical results and the experimental ones shows good agreement.